A variant at 9q34.11 is associated with HLA-DQB1*06:02 negative essential hypersomnia. Issue 12 (December 2018) - Miyagawa, Taku; Khor, Seik-Soon; Toyoda, Hiromi; Kanbayashi, Takashi; Imanishi, Aya; Sagawa, Yohei; Kotorii, Nozomu; Kotorii, Tatayu; Ariyoshi, Yu; Hashizume, Yuji; Ogi, Kimihiro; Hiejima, Hiroshi; et al.
Abstract Essential hypersomnia (EHS) is a lifelong disorder characterized by excessive daytime sleepiness without cataplexy. EHS is associated with human leukocyte antigen (HLA )-DQB1*06:02, similar to narcolepsy with cataplexy (narcolepsy). Previous studies suggest thatDQB1*06:02- positive and -negative EHS are different in terms of their clinical features and follow different pathological pathways.DQB1*06:02 -positive EHS and narcolepsy share the same susceptibility genes. In the present study, we report a genome-wide association study with replication forDQB1*06:02 -negative EHS (408 patients and 2247 healthy controls, all Japanese). One single-nucleotide polymorphism, rs10988217, which is located 15-kb upstream of carnitine O-acetyltransferase (CRAT ), was significantly associated withDQB1*06:02- negative EHS (P  = 7.5 × 10−9, odds ratio = 2.63). The risk allele of the disease-associated SNP was correlated with higher expression levels ofCRAT in various tissues and cell types, including brain tissue. In addition, the risk allele was associated with levels of succinylcarnitine (P  = 1.4 × 10−18 ) in human blood. The leading SNP in this region was the same in associations with bothDQB1*06:02 -negative EHS and succinylcarnitine levels. The results suggest thatDQB1*06:02 -negative EHS may be associated with an underlying dysfunction in energy metabolic pathways.